Climate drives shifts in grass reproductive phenology across the western USA. Issue 4 (21st November 2016) - Munson, Seth M.; Long, A. Lexine
Summary: The capacity of grass species to alter their reproductive timing across space and through time can indicate their ability to cope with environmental variability and help predict their future performance under climate change. We determined the long‐term (1895–2013) relationship between flowering times of grass species and climate in space and time using herbarium records across ecoregions of the western USA. There was widespread concordance of C3 grasses accelerating flowering time and general delays for C4 grasses with increasing mean annual temperature, with the largest changes for annuals and individuals occurring in more northerly, wetter ecoregions. Flowering time was delayed for most grass species with increasing mean annual precipitation across space, while phenology–precipitation relationships through time were more mixed. Our results suggest that the phenology of most grass species has the capacity to respond to increases in temperature and altered precipitation expected with climate change, but weak relationships for some species in time suggest that climate tracking via migration or adaptation may be required. Divergence in phenological responses among grass functional types, species, and ecoregions suggests that climate change will have unequal effects across the western USA. Abstract : See also the Commentary on this article by Primack & Gallinat, 213 : 1567–1568 .